Political Determinants of Indian Social Development - Avinash Kaza
The relationship between democracy and development is an ambiguous one. It would appear that in a country such as India, with a significant proportion of poor people, democracy could be used to reduce poverty and improve education and health. However, India's record on social development has been mediocre, especially relative to its authoritarian neighbor, China. India's aggregate indicators belie vast regional disparities in social development. For example, state literacy rates range from about 50 per cent to 90 per cent Given India's federal structure, in which states have a major role to play in social development, I examine if state- level politics explains some of India's regional disparities and develop a model showing the relationship between the electorate and the ruling party. Using a panel data set for the sixteen major states of India spanning the last four decades, I use an econometric framework to see if state- level political variables such as voter turnout, female representation, and degree of political competition make a difference in development expenditures and social development. The results demonstrate that these political variables do matter. States with greater political competition have increased their development budgets, and states with more female representation have decreased infant mortality rates the most rapidly. Voter turnout also appears to matter in reducing urban poverty. The results suggest that democracy can be used to enhance social development and improve the quality of life, although there is no automatic link.